First Report of Colletotrichum gloeosporioides Causing Leaf Spot Disease on Areca Palm (Chrysalidocarpus lutescens H. Wendl.) in India - Desai, Disha D.; Patel, P. R.; Prajapati, V. P. (International Journal of Economic Plants, 2019)
Colletotrichum gloeosporioides is known to have a wide host range and has become progressively more important pathogen on many economic crops worldwide. C. gloeosporioides was isolated for the first time from areca palm (Chrysalidocarpus lutescens H. Wendl.) in south Gujarat region. C. gloeosporioides was classified based on the morphological characteristics. To the best of our knowledge, this is the first report of C. gloeosporioides causing leaf spot of areca palm in India.